Antiepileptic Drugs and Bone Metabolism in Children: Data from 128 Patients. (February 2013) - Borusiak, Peter; Langer, Thorsten; Heruth, Marion; Karenfort, Michael; Bettendorf, Ulrich; Jenke, Andreas CW
There are conflicting results concerning bone metabolism in children receiving antiepileptic medication, with data concentrating on neurologically impaired patients. We performed a multicenter cross-sectional study in otherwise healthy children who received monotherapy with valproic acid, oxcarbazepine, lamotrigine, sulthiame, levetiracetam, or topiramate for at least 6 months. Data on calcium, phosphorus, alkaline phosphatase, 25-OH vitamin D, and parathormone were collected. Among 128 patients, 24.4% had hypocalcemia, 25.4% hypophosphatemia, and 13.3% (n = 17) 25-OH vitamin D levels <10 ng/mL. All patients were clinically asymptomatic. Mean calcium concentrations were found to be significantly lower among the study population (2.41 mmol/L) compared with healthy controls (2.53 mmol/L). Lowest mean concentration was observed in patients treated with sulthiame followed by oxcarbazepine and valproic acid. No influence of calcium intake or therapy on bone metabolism was noted. Effects on bone metabolism of anticonvulsive monotherapy are not restricted to neurologically impaired children but also affect otherwise healthy children.